Dziennik wydarzeń jako technika kształtowania kompetencji komunikacyjnej w sytuacji dwujęzyczności (Conversatoria Linguistica, 2019)
More and more experience in working with bilingual children allows the KrakowMethod therapists effectively build two language systems in the mind of the bilingual child’s anddevelop his communicative competence in both languages by the technique of writing anddrawing a diary of events. The overriding function of the diary of events is to assist in the acquisitionand enrichment of the language.